AKTIVITAS PENGHISAP LEM FOX PADA ANAK REMAJA DI KELURAHAN KADIA KECAMATAN KADIA KOTA KENDARI - Rifain As At All Halili; Wa Ode Sifatu; La Janu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
This study aims to determine the activity of sucking glue fox conducted by some teenagers in the village Kadia Kendari. This study used the theory of Pierre Bourdieu practice. Data collection techniques emphasis on emic perspective through observation and interview techniques. The results showed that glue fox widely recognized as an adhesive by some youth in the Village Kadia turned out to have been abused by teenagers in this area. The glue used by smoking the illicit drug like methamphetamine. Such behavior is motivated their association with some punk kid who had earlier activity glue suck fox. Great curiosity and, encourage teenagers to try and do similar activities and cause hangover effects. Factors education and social conditions in a family environment that is uncomfortable and unfriendly, also contributing shape the behavior of the fox glue abuse. Keywords: inhale glue fox, teenage son.